The giant “penis” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx) - Gruppe, Axel; Aspöck, Ulrike (Zootaxa, 2020)
The coniopterygid fauna of the Neotropical region is poorly known. The most recent summary was provided by Martins (2019) who noted that 14 species were known from Peru. The subgenus Coniopteryx (Scotoconiopteryx) is endemic to the Neotropical region and comprises 36 species (Meinander 1972; Meinander & Penny 1982; Sziráki 2011; Martins & Amorim 2016, Sarmiento-Cordero & Contreras-Ramos 2019).